CONGREGATION SATISFACTION AND SERVICE QUALITY GKPS PASTORS - Purba, Hendi Saputra; Lubis, Rahmi (International Journal of Cultural and Social Science, 2025)
As servants of God entrusted with shepherding a congregation willing to serve, God calls us to fulfill the calling of proclaiming the good news (the Gospel) throughout the world. This message can be conveyed through words and deeds visible to the world, as a witness to them. This demonstrates that servants must be truly submissive to Christ, the owner of the Church. Anyone who claims to be a servant but teaches deviant teachings, disrupts the unity of the congregation, and fails to strengthen the faith of its members is not a servant of Christ, but rather a servant seeking to satisfy their own desires. This includes ensuring a match between the congregation's expectations and the experience gained from the services provided by the organization. If the congregation perceives that the service meets or even exceeds their expectations, then congregation satisfaction will be achieved. Therefore, conclusions can be drawn based on the dimensions of GKPS Pastor Service Quality and Congregation Satisfaction: Tangible Evidence, Reliability, Responsiveness, Assurance, and Empathy. To determine congregation satisfaction, we need to understand the quality of GKPS pastor service.